Clio in the business school: Historical approaches in strategy, international business and entrepreneurship. Issue 6 (18th August 2017) - Perchard, Andrew; MacKenzie, Niall G.; Decker, Stephanie; Favero, Giovanni
Abstract: On the back of recent and significant new debates on the use of history within business and management studies, we consider the perception of historians as being anti-theory and of having methodological shortcomings; and business and management scholars displaying insufficient attention to historical context and privileging of certain social science methods over others. These are explored through an examination of three subjects: strategy, international business and entrepreneurship. We propose a framework for advancing the use of history within business and management studies more generally through greater understanding of historical perspectives and methodologies.